Liquid Nonlinear Oscillations in the U-Tube System - Kazachkov, A. R.; Lykah, V. A.; Minakova, K. A.; Syrkin, E. S.; Tkachenko, O. Y. (NTU "KhPI", 2016)
Dynamics of oscillation processes in a siphon U-tube is studied for the system of connected vessels filled with homogeneous liquid. The equations and phase paths describing the motion of viscous and non-viscous liquids are given, oscillation frequencies are considered. Oscillations are nonlinear in general case, but they turn into linear by setting specific parameter values of the system. Phase portraits are obtained and their dependences on parameters of the system are analyzedfor both linear and non-linear cases.
Keywords: communicating vessels; oscillations of liquid; linear motion equations; phase portraits; non-linear motion equations